2020
DOI: 10.1016/j.jclepro.2019.118473
|View full text |Cite
|
Sign up to set email alerts
|

The yoga of sustainable diets: Exploring consumers mind and spirit

Abstract: Unsustainable food choice and dietary behaviors put pressure on ecosystems and supply chain structures worldwide. Knowledge on the intrinsic values driving food consumption behavior are, therefore, essential in order to foster sustainability on a global, national and community based level. This study aims at exploring the relationship between different food consumption related behaviors and the intrinsic value shaping constructs of spirituality and mindfulness. Online questionnaire data on self-reported dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
1
18
1
Order By: Relevance
“…They established that spirituality and mindfulness are indeed independent constructs, but that some spirituality traits might overlap with aspects from mindfulness, such as the awareness of the external environment and nature. Werner et al (2020) also identify that natural spirituality, as lived in daily activities and the contact with nature, is associated with more sustainable dietary behaviours.…”
Section: Connectedness With Naturementioning
confidence: 94%
See 2 more Smart Citations
“…They established that spirituality and mindfulness are indeed independent constructs, but that some spirituality traits might overlap with aspects from mindfulness, such as the awareness of the external environment and nature. Werner et al (2020) also identify that natural spirituality, as lived in daily activities and the contact with nature, is associated with more sustainable dietary behaviours.…”
Section: Connectedness With Naturementioning
confidence: 94%
“…Another aspect often mentioned as pivotal for personal well-being is a high level of self-compassion, which has seen increases after mindfulness training (Neff et al 2007). Werner et al (2020) found that a supportive mindset, marked by the ability to decentre from thoughts and cultivate self-compassion, is positively associated with improved PEB, dietary awareness and informed food choice.…”
Section: Personal Health and Subjective Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…These savings in GHG emissions amount to approximately one third of the world's emissions in 2011 (Department of Energy and Cimate Change, 2015). This is reflected by a growing number of publications studying the relation between mindfulness and sustainable eating (Jacob et al, 2009;Fung et al, 2016;Böhme et al, 2018;Geiger et al, 2019a;Hunecke and Richter, 2019;Stanszus et al, 2019;Werner et al, 2020). Fung et al (2016) proposed a theoretical model where mindful eating is expected to improve the "awareness of the relationships between food and body, feelings, mind and interconnectedness between humans and the environment" (Fung et al, 2016(Fung et al, , p. 1084, postulating that mindfulness should help maintaining both personal and planetary health.…”
Section: Can Mindfulness Promote Sustainable Diets?mentioning
confidence: 99%
“…These savings in GHG emissions amount to approximately one third of the world’s emissions in 2011 ( Department of Energy and Cimate Change, 2015 ). This is reflected by a growing number of publications studying the relation between mindfulness and sustainable eating ( Jacob et al, 2009 ; Fung et al, 2016 ; Böhme et al, 2018 ; Geiger et al, 2019a ; Hunecke and Richter, 2019 ; Stanszus et al, 2019 ; Werner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%